Report of the Steering Committee on Family Welfare for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 1954)
The Report of the Steering Committee on Family Welfare for the Tenth Five-Year Plan (2002–2007), prepared by the Planning Commission, provides a comprehensive review of India’s demographic trends, family welfare strategies, and health system performance in the context of accelerating population stabilization and improving maternal and child health outcomes. Recognizing that human development and quality of life are central planning objectives, the report traces the evolution of India’s Family Welfare Programme since its historic launch in 1952 as the world’s first national family planning initiative, and assesses progress achieved during successive Five-Year Plans. It analyzes population projections based on Census 2001 data, highlighting variations in fertility decline across states and emphasizing the challenges posed by high population growth in certain regions. The report evaluates the shift during the Ninth Plan toward decentralized, district-based planning and the implementation of the Reproductive and Child Health (RCH) approach, alongside intensified efforts such as the pulse polio campaign. While acknowledging improvements in crude death rates, immunization coverage, institutional deliveries, and contraceptive use in several states, it notes that targets for birth rate reduction, maternal mortality, and infant mortality were not fully achieved. The document underscores the objectives of the National Population Policy 2000—meeting unmet needs for contraception, achieving replacement level fertility, and attaining population stabilization by 2045—and highlights the establishment of the National Population Commission under the Prime Minister to ensure coordinated implementation. Concluding with policy recommendations for the Tenth Plan, the report advocates strengthened public health infrastructure, enhanced private sector participation, improved monitoring and evaluation systems, and integrated, need-based strategies to accelerate demographic transition and promote equitable health and family welfare outcomes across the country.
Government of India Planning Commission September 2002
Keywords: Family Welfare Programme; Tenth Five-Year Plan; National Population Policy 2000; Demographic Transition; Population Projections; Reproductive And Child Health; Maternal And Child Health; Replacement Level Fertility; National Population Commission; Decentralized Planning; Contraceptive Services; Public Health Infrastructure